2017
DOI: 10.1155/2017/7191856
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Novel Twin Compounds Containing Tetramethylpyrazine and Carnitine Substructures in Experimental Ischemic Stroke

Abstract: Although studies have seen dramatic advances in the understanding of the pathogenesis of stroke such as oxidative stress, inflammation, excitotoxicity, calcium overload and apoptosis, the delivery of stroke therapies is still a great challenge. In this study, we designed and synthesized a series of novel twin compounds containing tetramethylpyrazine and carnitine substructures and explored their therapeutic potential and mechanism in stroke-related neuronal injury. We first screened the neuroprotective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Pharmacologic studies have demonstrated that Tetramethylpyrazine (TMP, also known as Ligustrazine), an intravenous drug made from traditional Chinese herbs, is able to reduce inflammatory responses [39] and activation of apoptosis [40]. It is capable of attenuating the severity of AP and protecting multiple organ injury in rats with AP [41].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic studies have demonstrated that Tetramethylpyrazine (TMP, also known as Ligustrazine), an intravenous drug made from traditional Chinese herbs, is able to reduce inflammatory responses [39] and activation of apoptosis [40]. It is capable of attenuating the severity of AP and protecting multiple organ injury in rats with AP [41].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the short in vivo half-life of tetramethylpyrazine, a novel compound containing tetramethylpyrazine and carnitine structures was synthesized. Further in vivo and in vitro results also confirmed that its anti-hypoxic brain protective effect was related to anti-oxidative stress and anti-inflammatory, ultimately maintaining the morphology and function of neurons and inhibiting neuronal apoptosis (Wang et al, 2017). Of course, there are other natural compounds that antagonize ischemiainfuriated morphological and functional disorders of brain mitochondria by regulating oxidative stress signals such as leonurine (Loh et al, 2010) and neferine .…”
Section: Monomers and Molecular Mechanisms In Regulating Mptp Opennesmentioning
confidence: 74%
“…Previous studies have demonstrated that pro-resolving lipid mediators such as maresins can protect tissues by suppressing damaging inflammation (Sun et al 2017 ). Therefore, we examined the serum levels of inflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the level of tissue MDA, a main product of lipid peroxidation, was markedly decreased in the MaR1-treated mouse livers following hepatic I/R insult. The eradication of reactive free radicals is dependent on many different antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT), which keep the balance between antioxidative effects and oxidative stress responses (Sun et al 2017 ). Loss of antioxidant enzymes causes accumulation of free radicals, which further exacerbates I/R-induced injury (Han et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%